THE RELATIONSHIP BETWEEN KNOWLEDGE AND MANAGEMENT COMMITMENT WITH COMPLIANCE WITH THE USE OF PPE FOR HEIGHT WORKERS IN THE SAVYAVASA LUXURY RESIDENCE PROJECT IN 2024 - Ronaldi Muhamad Farhan; Azizah Zen; Dihartawan; Triana Srisantyorini (Muhammadiyah International Public Health and Medicine Proceeding, 2024)
Work accidents hurt workers' performance, therefore the K3 program created and the K3 culture embedded in workers aims to reduce the number of work accidents and improve workers' performance. Worker compliance can be a factor that can have a positive impact on work safety. Data from BPJS Employment shows that the national number of work accidents in 2021 was 7,298 work accident cases in general and 417 cases in the city of DKI Jakarta in particular, 49 of which were due to falls from heights. The purpose of this study is to ascertain how high-altitude workers at The Savyavasa Luxury Residence Project in 2024 relate to management knowledge, commitment, and PPE use compliance. The purpose of this study is to determine the association between management knowledge and commitment and use compliance using quantitative methodologies and a cross-sectional approach. PPE for workers at heights. Seventy employees of The Savyavasa Luxury Residence Project in 2024 made up the study's population. The study's findings indicate a correlation between management commitment and PPE use compliance (p-value = 0.006) as well as a correlation between knowledge and PPE usage compliance (p-value = 0.040). The conclusion that can be made is that management commitment, awareness, and compliance with the usage of personal protective equipment (PPE) for high-altitude workers are related. Employee education, workplace inspections, and the assessment and management of current issues by business regulations are all expected of the organization.